Preparation method and application of ruthenium-doped nickel-iron-based heterostructure catalyst

By synthesizing nickel-iron-based heterostructures on the foam nickel substrate and doping ruthenium to form a ruthenium-doped nickel-iron-based heterostructure catalyst, the problem of insufficient activity and durability of existing non-precious metal electrocatalysts is solved, and excellent HER and OER catalytic performance is achieved.

CN119913558AActive Publication Date: 2025-05-02KUNMING UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510094453.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-05-02
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

Existing non-precious metal electrocatalysts are still insufficient in terms of electrocatalytic activity and durability of total water removal, and improvements are needed to achieve excellent HER and OER catalytic properties.

Method used

Nickel foam as the substrate is used to synthesize the nickel-iron-based heterostructure NiFe2O4-Ni(OH)2 by hydrothermal method, and dopant low-quality noble metal ruthenium-doped heterostructure catalyst by impregnation method to form a ruthenium-doped nickel-iron-based heterostructure catalyst.

Benefits of technology

The catalytic activity and stability of the catalyst are significantly improved, the electronic structure and adsorption energy of the electrochemical reaction intermediate are optimized, and the conductivity and reactivity of the catalyst are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005252468460000011
    Figure HDA0005252468460000011
  • Figure HDA0005252468460000012
    Figure HDA0005252468460000012
  • Figure HDA0005252468460000021
    Figure HDA0005252468460000021
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a ruthenium-doped ferronickel-based heterostructure catalyst. The preparation method disclosed by the invention comprises the following steps: dissolving oxalic acid and ferric salt in water to obtain an iron precursor solution; the foamed nickel is placed in the iron precursor solution for a hydrothermal reaction, and a nickel-iron-based heterostructure is formed on the foamed nickel; the foamed nickel with the nickel-iron-based heterostructure is placed in a ruthenium salt solution to be subjected to an impregnation reaction, the ruthenium-doped nickel-iron-based heterostructure catalyst is obtained, and ruthenium is doped in crystal lattices of the nickel-iron-based heterostructure. The ruthenium-doped ferronickel-based heterostructure catalyst prepared by the invention can be applied to an electro-catalytic water splitting reaction, and has good electro-catalytic complete water splitting performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a low-load ruthenium-doped nickel-iron-based heterostructure catalyst and application thereof in an electrocatalytic water decomposition reaction. Background Art

[0002] Hydrogen is the most promising green energy source in the future. Electrochemical water splitting is an attractive technology in the field of energy conversion because it can produce H2 and O2 simultaneously in a clean and safe way without emitting carbon dioxide. In addition, although the theoretical voltage of electrocatalytic water splitting is 1.23V, the actual required cell voltage is often greater than 1.23V. Therefore, it is of great significance to explore bifunctional electrocatalysts with excellent HER and OER catalytic performance, as well as good stability and economy.

[0003] Transition metal-based electrocatalysts with three-dimensional orbitals have attracted great interest from researchers due to their similar properties to those of precious metal-based catalysts. Many transition metal-based electrocatalysts have been developed, including transition metal oxides / hydroxides, nitrides, carbides, and phosphides. Oxides or hydroxides of transition metal catalysts have been some of the most common OER catalysts, among which nickel-based and iron-based electrocatalysts have attracted widespread attention due to their abundant reserves, excellent catalytic activity, and low cost. Under alkaline conditions, nickel iron oxide or nickel hydroxide exhibits excellent catalytic activity for the oxygen evolution reaction (OER) and has a strong ability to adsorb oxygen-containing intermediates. Since Ni atoms and water molecules easily form Ni-O bonds of optimal strength, the adsorption of intermediates is beneficial, thereby accelerating the OER process, which makes metallic nickel iron-based materials excellent OER catalysts in alkaline solutions, and also promotes the dissociation of water in the hydrogen evolution reaction (HER).

[0004] However, compared with precious metal catalysts, these non-precious metal electrocatalysts are still insufficient in terms of electrocatalytic activity and durability for overall water splitting and need to be improved. Summary of the invention

[0005] In order to at least partially solve the problems of the prior art, the first aspect of the present invention discloses a method for preparing a ruthenium-doped nickel-iron-based heterostructure catalyst, comprising the following steps:

[0006] dissolving oxalic acid and iron salt in deionized water to obtain an iron precursor solution;

[0007] Placing the nickel foam in the iron precursor solution for hydrothermal reaction to form a nickel-iron based heterostructure on the nickel foam;

[0008] The nickel foam formed with a nickel-iron-based heterostructure is placed in a ruthenium salt solution for immersion reaction, and after cleaning and drying, a ruthenium-doped nickel-iron-based heterostructure catalyst is obtained, wherein ruthenium is doped inside the lattice of the nickel-iron-based heterostructure.

[0009] Furthermore, the temperature of the hydrothermal reaction is 120-220°C, and the time is 6-12 hours. Preferably, the temperature of the hydrothermal reaction is 200°C, and the time is 7 hours.

[0010] Furthermore, the impregnation reaction time is 3-12 hours, preferably 5 hours.

[0011] Furthermore, the molar concentration of the ruthenium salt solution is 0.0005-0.01 mM, preferably 0.001-0.008 mM, for example 0.005 mM.

[0012] Furthermore, the molar concentration of oxalic acid in the iron precursor solution is 0.01-0.1M, preferably 0.02-0.08M, for example 0.06M; the molar concentration of iron salt in the iron precursor solution is 0.01-0.08M, preferably 0.02-0.05M, for example 0.03M.

[0013] Furthermore, the iron salt is iron nitrate or iron chloride, and the ruthenium salt is ruthenium chloride.

[0014] The second aspect of the present invention discloses the use of the ruthenium-doped nickel-iron-based heterostructure catalyst prepared by the above method in the electrocatalytic water decomposition reaction.

[0015] The technical solution of the present invention has the following beneficial effects:

[0016] (1) Nickel foam was used as the substrate, and a nickel-iron-based heterostructure NiFe2O4-Ni(OH)2 was synthesized by a hydrothermal method; the introduction of Fe can improve the catalytic activity and stability of nickel-based oxides and hydroxides. Under alkaline conditions, nickel-iron oxide and nickel hydroxide have a strong ability to adsorb oxygen-containing intermediates and have excellent catalytic activity for the oxygen evolution reaction (OER), while also promoting the dissociation of water in the hydrogen evolution reaction (HER).

[0017] (2) The present invention can dope ruthenium into the lattice of the nickel-iron-based heterostructure NiFe2O4-Ni(OH)2. On the one hand, a strong electronic interaction is formed between Ru and Ni and Fe, which can adjust the electronic structure of the electrochemical reaction intermediate and optimize its adsorption energy. On the other hand, the doped Ru atoms not only act as efficient active sites to synergize with the host material to promote the electrocatalytic reaction, but also change the microstructure of the material, resulting in more lattice distortion of the nickel-iron-based heterostructure NiFe2O4-Ni(OH)2, exposing more active sites, thereby significantly improving the catalytic activity and stability of the catalyst.

[0018] ⑶ After ruthenium is doped into the lattice of the nickel-iron-based heterostructure NiFe2O4-Ni(OH)2, electrons are transferred from Fe and Ni to Ru, reducing the oxidation state of Ru, solving the serious problem that the Ru active sites in the precious metal catalyst are often oxidized to a high-valent state and dissolved into the electrolyte during a long OER reaction, resulting in reduced stability.

[0019] In order to more clearly illustrate the purpose, technical solutions and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the XRD pattern of the catalyst of Example;

[0021] Figure 2 In the figure: a is the Ru 3p XPS spectrum of the catalyst of the embodiment, b is the Fe 2p XPS spectrum of the catalyst of the embodiment and the comparative example, c is the Ni 2p XPS spectrum of the catalyst of the embodiment and the comparative example, and d is the O1s XPS spectrum of the catalyst of the embodiment and the comparative example;

[0022] Figure 3 Middle: a and b are SEM images of the catalyst of the embodiment, and c and d are TEM images thereof;

[0023] Figure 4 Middle: a and b are SEM images of comparative catalysts, and c and d are TEM images thereof;

[0024] Figure 5 In the figure: a is a comparison of the HER linear sweep voltammetry (LSV) curves of the embodiment, the comparative example and the commercial Pt / C catalyst, b is a comparison of its Tafel slope, and c is its double layer capacitance (C dl ) is a comparison diagram, d is a HER chronovoltage curve (CP) diagram of the catalyst of the embodiment;

[0025] Figure 6 In the figure: a is a comparison of the OER linear sweep voltammetry (LSV) curves of the embodiment, comparative example and commercial RuO2 catalyst, b is a comparison of its Tafel slope, and c is its double layer capacitance (C dl ) is a comparison diagram, d is an OER timing voltage curve (CP) diagram of the catalyst of the embodiment;

[0026] Figure 7 Middle: a is a comparison diagram of the overall water splitting LSV of the embodiment and the commercial catalyst, b is a Faraday efficiency diagram (FE) of the embodiment catalyst;

[0027] Figure 8 is a graph of the complete water splitting chronopotentiometry (CP) curve of the catalyst of the embodiment;

[0028] Fig. 9 is a comparison chart of oxygen vacancy contents of catalysts of Example and Comparative Example;

[0029] Fig.10 It is a comparison diagram of the hydrophilic contact angles of the example catalyst and pure nickel foam. DETAILED DESCRIPTION

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other variations or replacements made on this basis. Therefore, other possible implementation methods that may be known to those skilled in the art based on the embodiments described in this application all belong to the protection scope of the present invention.

[0031] The embodiment of the present invention discloses a method for in-situ growing an FN heterostructure (nickel-iron-based heterostructure) on a nickel foam substrate by a hydrothermal method, and then doping a low amount of precious metal ruthenium by an impregnation method to obtain an RFN catalyst (ruthenium-doped nickel-iron-based heterostructure catalyst), comprising the following steps:

[0032] The nickel foam is cleaned on the surface. Specifically, the nickel foam can be placed in acetone, hydrochloric acid solution and deionized water for ultrasonic cleaning in sequence to clean the surface, wherein acetone can prevent organic impurities from remaining on the surface of the nickel foam, and the hydrochloric acid solution can remove oxides on the surface.

[0033] Dissolve an iron salt such as iron nitrate and oxalic acid in deionized water to obtain an iron precursor solution. The molar concentration of oxalic acid in the iron precursor solution is 0.01 to 0.1 M, preferably 0.02 to 0.08 M, such as 0.06 M; the molar concentration of the iron salt is 0.01 to 0.08 M, preferably 0.02 to 0.05 M, such as 0.03 M.

[0034] The cleaned nickel foam is placed in an iron precursor solution for hydrothermal reaction to obtain a FN heterostructure, wherein the hydrothermal reaction temperature may be 120 to 220° C. and the reaction time may be 6 to 12 hours.

[0035] The ruthenium salt is dissolved in deionized water to obtain a ruthenium salt solution, wherein the molar concentration of the ruthenium salt solution is 0.0005-0.01 mM, preferably 0.001-0.008 mM, for example 0.005 mM.

[0036] The nickel foam forming the FN heterostructure is placed in a ruthenium salt solution for impregnation reaction, and the RFN heterostructure catalyst is obtained after washing and drying. The impregnation time can be 3-12 hours.

[0037] The following is a detailed description with reference to the embodiments and comparative examples.

[0038] Example (RFN Catalyst)

[0039] (1) The nickel foam (2.5 cm*3 cm) was ultrasonically cleaned in acetone, 6.0 M hydrochloric acid solution and deionized water for 30 minutes, and then dried to obtain a clean nickel foam substrate. The thickness of the nickel foam was 1.6 mm and the pore size was 110 ppi.

[0040] ⑵ First, add 225 mg of oxalic acid and 485 mg of Fe(NO3)3·9H2O to 40 mL of deionized water and stir at room temperature for 300 s. Then transfer the uniformly dissolved solution to a Teflon autoclave (the molar concentration of oxalic acid in the solution is 0.06 M, and the molar concentration of Fe(NO3)3 is 0.03 M).

[0041] ⑶ Place the cleaned nickel foam horizontally at the bottom of the Teflon high-pressure reactor liner, then place the reactor in a forced air drying oven, set the temperature to 200°C, and keep it warm for 7 hours.

[0042] (4) The product obtained after the reaction was washed three times with deionized water and anhydrous ethanol in sequence, and then placed in a vacuum drying oven at 60°C for 6 h.

[0043] ⑸ The nickel foam with FN heterostructure formed in step ⑷ was placed in 30 mL aqueous solution containing 24 mg RuCl3·xH2O (the molar concentration of RuCl3 in the solution was 0.005 mM), immersed for 5 h, rinsed three times with deionized water and anhydrous ethanol in sequence, and then placed in a vacuum drying oven at 60°C for 6 h to obtain an RFN catalyst.

[0044] Comparative Example (NF Catalyst)

[0045] The difference between the preparation of the comparative example and the example is that step (5) of the example is not included, that is, no ruthenium doping is introduced.

[0046] Morphology, size and phase analysis of examples and comparative examples

[0047] Figure 1 The X-ray diffraction (XRD) spectrum of the embodiment RFN catalyst verifies the crystal structure and composition. Among them, a series of strong diffraction peaks at 18.6°, 33.1°, 38.3°, and 51.6° at 2θ are attributed to Ni(OH)2 (PDF#73-1520), and a series of strong diffraction peaks at 17.6°, 30.1°, 35.6°, 44.3°, and 62.7° are attributed to NiFe2O4 (PDF#44-1485). It is worth noting that no diffraction peak of Ru was found in the spectrum.

[0048] Figure 2 : is the XPS spectrum of the catalyst of the embodiment and the comparative example. Specifically, Figure 2a shows the Ru 3p XPS spectrum of the example RFN catalyst, where the two peaks at 462.3 and 484.9 eV correspond to Ru 4+ , while the two peaks at 464.7 and 487.9 eV correspond to Ru 3+ . Figure 2 The XPS spectrum of Fe 2p in b can be divided into two peaks, corresponding to Fe 3+ 2p 3 / 2 and Fe 3+ 2p 1 / 2 track. Figure 2 c shows the Ni 2p XPS spectrum, where the two peaks correspond to Ni 2+ 2p 3 / 2 and Ni 2+ 2p 1 / 2 orbit, and the remaining two peaks are satellite peaks. Figure 2 d shows the O1s XPS spectrum, in which the three peaks are attributed to hydroxyl (OH), unsaturated oxygen, and lattice oxygen (MO). Figure 2 The test results show that RFN heterostructure (ruthenium-doped nickel-iron-based heterostructure) was in situ grown on the surface of nickel foam through hydrothermal and impregnation treatment processes.

[0049] Figure 3 a and b are field emission scanning electron microscope (FE-SEM) images of the RFN catalyst of Example, from which it can be seen that the RFN heterostructure grown in situ on the nickel foam forms uniform three-dimensional nanosheets. Figure 3 c and d are transmission electron microscope (TEM) images, which confirm the nanosheet structure and size of the RFN catalyst in Example 1. Figure 3 d High-resolution transmission electron microscopy (HRTEM) image shows two different lattice fringes with lattice spacings of 0.108 nm and 0.104 nm, corresponding to the (001) crystal plane of Ni(OH)2 and the (111) crystal plane of NiFe2O4, respectively.

[0050] Figure 4 a and b are field emission scanning electron microscope (FE-SEM) images of the comparative FN catalyst. It can be seen that the FN heterostructure in the comparative example is also in the shape of a three-dimensional nanosheet, indicating that the introduction of Ru does not affect the morphology of the FN heterostructure. Figure 4 c and d are transmission electron microscope (TEM) images of the comparative FN catalyst, where Figure 4 The high-resolution transmission electron microscopy (HRTEM) image of (d) shows two different lattice fringes with lattice spacings of 0.108 nm and 0.104 nm, corresponding to the (001) crystal plane of Ni(OH)2 and the (111) crystal plane of NiFe2O4, respectively.

[0051] Combined with the above analysis, on the one hand, Figure 2 The XPS spectrum of a can prove that Ru is successfully introduced, and Figure 3 No obvious Ru phase was observed in the SEM and TEM images. Figure 1 There is no diffraction peak of Ru in the XRD spectrum of Figure 1 The negative shift of NiFe2O4 and Ni(OH)2 peaks in the XRD pattern relative to the corresponding diffraction peaks of the standard card is sufficient to prove that Ru is doped into the lattice of the NiFe2O4-Ni(OH)2 heterostructure.

[0052] Since the physical properties and radius sizes of ruthenium (Ru) and nickel (Ni) atoms are similar, ruthenium atoms are allowed to effectively penetrate and replace nickel atomic sites. The unique three-dimensional sheet configuration of the NiFe2O4-Ni(OH)2 heterostructure provides conditions for Ru to be incorporated into the lattice. Therefore, nickel replacement can be achieved by immersing the NiFe2O4-Ni(OH)2 heterostructure in a ruthenium solution. Ru atoms can be incorporated into the lattice of NiFe2O4 and Ni(OH)2 without significantly changing the structure of the matrix material.

[0053] Electrocatalytic performance test of examples and comparative examples

[0054] The three-electrode system test conditions are as follows: the test is conducted in a 1 mol / L KOH solution saturated with N2; the reference electrode is an Ag / AgCl electrode, and the counter electrode is a Pt sheet electrode.

[0055] The test conditions for complete water splitting were as follows: the test was conducted in a 1 mol / L KOH solution saturated with N2; wherein the reference electrode and the counter electrode were both the catalysts prepared in the examples.

[0056] Figure 5 a is a comparison of the linear sweep voltammetry (LSV) curves of the embodiment, the comparative catalyst and the commercial Pt / C catalyst. It can be seen that the RFN catalyst of the embodiment has significantly enhanced HER activity and shows the lowest overpotential; specifically, the RFN catalyst has a significantly enhanced HER activity at 10 mA cm -2 The HER overpotential is 15 mV at 100 mA cm -2 The HER overpotential is 124 mV, and the catalytic activity is significantly better than that of FN and commercial Pt / C. Figure 5 b Comparison of the Tafel slopes of the three catalysts. It can be seen that the RFN catalyst exhibits the lowest Tafel slope (59.66 mV dec) at high current density. -1 ), which indicates that the RFN catalyst has faster reaction kinetics. Figure 5 c is the double layer capacitance (C) used to estimate the electrochemical surface area (ECSA) dl ) Comparison chart, C of RFN catalyst dl17.95mFcm -2 , which is much higher than that of other samples, indicating that it can provide more active sites in the OER process. Figure 5 d is the chronopotentiometry (CP) curve of the RFN catalyst at 100 mA cm -2 The catalytic activity of the RFN catalyst hardly decayed after operating continuously for more than 532 hours at an industrial-grade current density.

[0057] Figure 6 Figure a is a comparison of the linear sweep voltammetry (LSV) curves of the embodiment, the comparative catalyst and the commercial Ru2O catalyst, in which the OER performance of the RFN catalyst is significantly better than that of the FN and commercial Ru2O catalysts. Specifically, at 10 mA cm -2 The OER overpotential of the RFN catalyst is 248 mV at 100 mA cm -2 The OER overpotential of the lower RFN catalyst is 308 mV, showing the lowest overpotential. Figure 6 b is the comparison of the Tafel slopes of the three catalysts. The RFN catalyst exhibits the lowest Tafel slope (24.54 mV dec) at high current density. -1 ), which indicates that the RFN catalyst has faster reaction kinetics. Figure 6 c is the double layer capacitance of the three (C dl ) Comparison chart, C of RFN catalyst dl 17.95mF cm -2 , which is higher than that of the comparative FN catalyst, indicating that it can provide more active sites in the OER process. Figure 6 d is the chronovoltage curve (CP) of the RFN catalyst of Example 1, at 100 mA cm -2 The catalytic activity of the RFN catalyst hardly decayed after working continuously for more than 3940 hours at an industrial-grade current density.

[0058] Figure 7 a is a comparison of the LSV of the complete water splitting of the RFN catalyst in the embodiment and the commercial catalyst. The RFN catalyst in the embodiment only needs 1.498V and 1.665V voltages to reach 10mA cm -2 and 100mA cm -2 The current density is much higher than that of commercial catalysts. Figure 7 b is the Faraday efficiency (FE) of the RFN catalyst calculated by the hydrogen production efficiency test system. By comparing the theoretical gas production and the actual gas production at different times, the volume ratio of H2 to O2 was measured to be 2:1. The calculated FE of the overall water decomposition of the RFN catalyst is close to 100%, showing its excellent catalytic activity. Figure 8The chronopotentiometry (CP) curve of the RFN catalyst in Example 1 is shown at 100 mA cm -2 The catalytic activity of the RFN catalyst hardly decayed after operating continuously for more than 540 hours at a current density of 1.34 W.

[0059] Oxygen vacancy content test of examples and comparative examples

[0060] from Figure 2 d, the unsaturated oxygen intensity in the RFN catalyst of the embodiment is higher than that in the FN catalyst of the comparative example, and the unsaturated oxygen is related to oxygen vacancies, which indicates that the RFN catalyst may be richer in oxygen vacancies. In order to further confirm the existence of oxygen vacancies, the RFN and FN catalysts were tested using electron paramagnetic resonance (EPR) technology.

[0061] Fig. 9 In the graph, a strong signal corresponding to oxygen vacancies was observed for both RFN and FN catalysts at g = 2.003. Importantly, the EPR signal of the RFN catalyst is stronger than that of the FN catalyst, indicating that there are more abundant oxygen vacancies in the RFN catalyst, which is consistent with the XPS results. Abundant oxygen vacancies can enhance the conductivity of the electrocatalyst, facilitate the adsorption and dissociation of water and electrochemical reaction intermediates, thereby optimizing the binding strength of the reaction intermediates and improving the electrocatalytic performance of the RFN catalyst.

[0062] Hydrophilicity Test of Examples

[0063] Fig.10 In the study, the surface properties of the RFN catalyst were revealed by measuring the contact angles of the RFN catalyst and the pure nickel foam (NF) substrate at the solid-liquid and solid-gas interfaces, which is closely related to the improvement of the catalytic performance at high current density. Among them, the contact angle of pure nickel foam is 115.63°, indicating that pure nickel foam is a hydrophobic material. In contrast, the contact angle of the FN catalyst is 0°, indicating that the RFN catalyst is super hydrophilic. The strong wettability of the RFN catalyst is conducive to the contact between the solution and the material surface, thereby accelerating its reaction kinetics and improving the electrocatalytic efficiency.

[0064] In summary, the RFN catalyst of the present invention is applied to the electrocatalytic complete water splitting reaction. The nickel-iron oxide and hydroxide themselves have good OER catalytic performance. The strong electronic effect between Ru and Fe and Ni regulates the electronic structure of the active site, optimizes the adsorption energy of the reaction intermediates, and transfers electrons from Fe and Ni to Ru, inhibiting the over-oxidation of Ru and improving the catalytic activity and stability of the catalyst. The superhydrophilicity of the RFN catalyst enables it to have good contact with the electrolyte, thereby accelerating the reaction kinetics and improving the electrocatalytic efficiency; the abundant oxygen vacancies enhance the conductivity of the electrocatalyst, which is beneficial to the adsorption and dissociation of water and other electrochemical reaction intermediates, thereby optimizing the binding strength of the reaction intermediates. These favorable factors combine to improve the electrocatalytic performance of the RFN catalyst.

[0065] Although the present invention is described above through specific embodiments, it should be understood that any equivalent changes made by ordinary technicians in this field without departing from the scope of the present invention should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a ruthenium-doped nickel-iron-based heterostructure catalyst, comprising the following steps: dissolving oxalic acid and iron salt in water to obtain an iron precursor solution; Placing the nickel foam in the iron precursor solution for hydrothermal reaction to form a nickel-iron based heterostructure on the nickel foam; The nickel foam formed with a nickel-iron-based heterostructure is placed in a ruthenium salt solution for an impregnation reaction to obtain a ruthenium-doped nickel-iron-based heterostructure catalyst; wherein ruthenium is doped inside the lattice of the nickel-iron-based heterostructure.

2. The method for preparing a ruthenium-doped nickel-iron-based heterostructure catalyst according to claim 1; wherein: The temperature of the hydrothermal reaction is 120-220° C. and the time is 6-12 hours.

3. The method for preparing a ruthenium-doped nickel-iron-based heterostructure catalyst according to claim 2; wherein: The temperature of the hydrothermal reaction is 200° C. and the time is 7 hours.

4. The method for preparing a ruthenium-doped nickel-iron-based heterostructure catalyst according to claim 1; wherein: The impregnation reaction time is 3 to 12 hours.

5. The method for preparing a ruthenium-doped nickel-iron-based heterostructure catalyst according to claim 4; wherein: The impregnation reaction time is 5 hours.

6. The method for preparing a ruthenium-doped nickel-iron-based heterostructure catalyst according to claim 1; wherein: The molar concentration of the ruthenium salt solution is 0.0005-0.01 mM.

7. The method for preparing a ruthenium-doped nickel-iron-based heterostructure catalyst according to claim 1; wherein: The molar concentration of oxalic acid in the iron precursor solution is 0.01-0.1M, and the molar concentration of the iron salt is 0.01-0.08M.

8. The method for preparing a ruthenium-doped nickel-iron-based heterostructure catalyst according to claim 1; wherein: The iron salt is ferric nitrate or ferric chloride.

9. The method for preparing a ruthenium-doped nickel-iron-based heterostructure catalyst according to claim 1; wherein: The ruthenium salt is ruthenium chloride.

10. Use of the ruthenium-doped nickel-iron-based heterostructure catalyst obtained by the preparation method according to any one of claims 1 to 9 in an electrocatalytic water decomposition reaction.

Citation Information

Patent Citations

  • High-activity self-supporting OER electrocatalyst material as well as preparation method and application thereof

    CN113019398A

  • Preparation method of transition metal doped ruthenium-nickel hydroxide composite catalyst

    CN118028889A

  • Precious metal ruthenium doped ferronickel oxide / nickel oxide nanosheet electrolyzed water catalyst and preparation method thereof

    CN118147699A

  • Universal One-Step Method to Make Fe-Based (Oxy)Hydroxides as Efficient OER Catalysts for Seawater Electrolysis

    US20230010138A1

  • Preparation method for foamed nickel-based catalyst for hydrogen production by water electrolysis

    WO2021184563A1